Emerging therapeutics for the treatment of thrombotic thrombocytopenic purpura. (3rd October 2018) - Scully, Marie; Westwood, John Paul
ABSTRACT: Introduction : Thrombotic thrombocytopenic purpura (TTP) is an acute life-threatening condition, associated with a low platelet count, hemolytic anemia, fragmentation, and polychromasia on blood film and microvascular thrombi formation associated with multi-organ involvement. Mortality remains at 10–20%, but in those with neurological involvement and raised markers of cardiac damage – namely troponin – is much higher, acutely reaching 80–90%. TTP is the result of a severe deficiency of the metalloproteinase, ADAMTS 13. Areas covered : This review discusses the presentation of TTP, followed by current therapies used primarily in immune-mediated TTP but with reference to congenital TTP. Some of the issues relating to TTP outcomes have been presented. Current treatments, including plasma exchange and immunosuppression are discussed along with in-depth presentations of two new therapies for TTP. Expert opinion : Over the next few years, the treatment of TTP should be simplified with the availability of the antiv on Willebrand factorfactor antibody (caplacizumab) and recombinant ADAMTS 13. The need for intensive plasma exchange should be significantly reduced and morbidity and mortality decreased on the diagnosis of TTP. Immune therapy will still be required to reduce anti-ADAMTS 13 antibodies, aiming to normalize ADAMTS 13 activity. Currently, anti-CD20 therapy is the gold standard.